Global burden and cross-national inequalities of tobacco-attributable cancers in adults aged 40 and above, 1990–2021: a population-based study - Li, Yi; Li, Hui; Tang, Lirui; Chen, Chuanben; Huang, Chaoxiong (Frontiers in Oncology, 2025)
BackgroundTobacco exposure substantially increases the global cancer burden; however, studies targeting specific subgroups are scarce. We aimed to investigate global burden trends of tobacco-attributable cancers among people aged ≥40 and the associated cross-national inequalities based on the sociodemographic index (SDI).MethodsWe performed secondary analyses on data from the Global Burden of Disease (GBD) Study 2021. The global tobacco-attributable cancer burden was assessed by age-standardized (ASR)-disability adjusted life years (DALYs) and deaths. The estimated annual percentage changes were used to illustrate temporal global and regional trends from 1990 to 2021. Decomposition analyses determined the impact of population growth, aging, and epidemiological changes on disease burden. The slope inequality index (SII) and concentration index (CI) were used to quantify cross-country inequalities in the tobacco-attributable cancer burden.ResultsIn 2021, global tobacco-attributable ASR-DALYs among people aged ≥40 were 1,687.49 per 100,000 people, a continuous decline since 1990, and ASR deaths were 72.36 per 100,000 people. By 2030, they are projected to fall to 1,464.68 and 64.59 per 100,000, respectively. Men exhibited higher DALYs and deaths than women (40.8 million DALYs, 1.7 million deaths). The most prominent tobacco exposure was smoking (ASR-DALY: 1,603.98/100000). Among the 16 cancers observed, tracheal, bronchial, and lung cancers had significantly higher ASR-DALYs and ASR-related deaths than other cancers. Population growth was the main cause of the tobacco-attributable cancer burden, followed by epidemiological changes. The highest ASR-DALYs and deaths were observed in the medium-high SDI regions and the lowest in the low SDI regions. Health inequality analyses showed that the DALYs SII declined from 2,654/100,000 in 1990 to 1,178/100,000 in 2021; however, the difference between high and low SDI countries narrowed significantly. The DALYs CI was 0.17 in 1990 and 2021, and the mortality CI increased from 0.17 to 0.18.ConclusionsThe cancer burden attributable to tobacco use varied significantly according to sex, age, region, and SDI. The global tobacco-attributable cancer burden among people aged ≥40 has been declining since 1990, paralleling mitigated yet persistent cross-national inequalities. The study’s findings could help to develop strategies for improving the prevention and treatment of cancers.